2020
DOI: 10.1186/s41936-020-00149-z
|View full text |Cite
|
Sign up to set email alerts
|

Synergism of three botanical termiticides as wood protectants against subterranean termites, Macrotermes subhyalinus (Rambur, 1842)

Abstract: Background: The increased interest in the harmful effects of most chemical pesticides on the ecosystem has continually served as an impetus to search for safer and eco-friendly pesticides from plant origin. In this study, the termiticidal potentials of extract mixtures of Azadirachta indica (A. Juss.), Nicotiana tabacum (L.), and Jatropha curcas (L.) against Macrotermes subhyalinus (Rambur, 1842) infesting Triplochiton scleroxylon (K. Schum) wood blocks were investigated in the field (open and under shade) and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 28 publications
(28 reference statements)
0
1
0
Order By: Relevance
“…The ability of various plant based extracts observed now to elicit termite mortality is in agreement with earlier studies of Singh and Kumar (2008), Shiberu et al, (2013), andEkhuemelo et al (2017). However, the termite mortality rate depends on the caste of the termite, the chemical composition of the plant product, and exposure time (Ajayi et al, 2020). The higher potency of neem (fresh and fermented extracts) and tulsi (fermented extracts) to Odontotermes sp.…”
Section: Resultsmentioning
confidence: 99%
“…The ability of various plant based extracts observed now to elicit termite mortality is in agreement with earlier studies of Singh and Kumar (2008), Shiberu et al, (2013), andEkhuemelo et al (2017). However, the termite mortality rate depends on the caste of the termite, the chemical composition of the plant product, and exposure time (Ajayi et al, 2020). The higher potency of neem (fresh and fermented extracts) and tulsi (fermented extracts) to Odontotermes sp.…”
Section: Resultsmentioning
confidence: 99%
“…Worldwide, chemical insecticides are the main method used by farmers to overcome termite damages (Logan et al, 1990;Akutse et al, 2011;Otieno, 2018). However, synthetic termicides have harmful effects on human health and environment (Oladipo-nee Ajahi et al, 2020). Unfortunately, Loko et al (2019a) reported the use of highly hazardous chemical insecticides by Beninese farmers to fight termite pests in maize plantations.…”
Section: Introductionmentioning
confidence: 99%